Therapeutic mechanism of baicalein in peritoneal dialysis-associated peritoneal fibrosis based on network pharmacology and experimental validation - Lu, Xiaohui; Wu, Kefei; Jiang, Simin; Li, Yi; Wang, Yating; Li, Hongyu; Li, Guanglan; Liu, Qinghua; Zhou, Yi; Chen, Wei; Mao, Haiping (Frontiers in Pharmacology, 2023)
Baicalein (5,6,7-trihydroxyflavone) is a traditional Chinese medicine with multiple pharmacological and biological activities including anti-inflammatory and anti-fibrotic effects. However, whether baicalein has a therapeutic impact on peritoneal fibrosis has not been reported. In the present study, network pharmacology and molecular docking approaches were performed to evaluate the role and the potential mechanisms of baicalein in attenuating peritoneal dialysis-associated peritoneal fibrosis. The results were validated in both animal models and cultured human mesothelial cell line. Nine intersection genes among baicalein targets and the human peritoneum RNA-seq dataset including four encapsulating peritoneal sclerosis samples and four controls were predicted by network analysis. Among them, MMP2, BAX, ADORA3, HIF1A, PIM1, CA12, and ALOX5 exhibited higher expression in the peritoneum with encapsulating peritoneal sclerosis compared with those in the control, which might be crucial targets of baicalein against peritoneal fibrosis. Further, KEGG and GO enrichment analyses suggested that baicalein played an anti-peritoneal fibrosis role through regulating cell proliferation, inflammatory response, and AGE-RAGE signaling pathway. Moreover, molecular docking analysis revealed a strong potential binding between baicalein and MMP2, which was consistent with the predictive results. Importantly, using a mouse model of peritoneal fibrosis by intraperitoneally injecting 4.25% glucose dialysate, we found that baicalein treatment significantly attenuated peritoneal fibrosis, as evident by decreased collagen deposition, protein expression of α-SMA and fibronectin, and peritoneal thickness, at least, by reducing the expression of MMP2, suggesting that baicalein may have therapeutic potential in suppressing peritoneal dialysis-related fibrosis.